2022
DOI: 10.1002/advs.202104424
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neural Differentiation of ADMSCs using Graphene‐Mediated Wireless‐Localized Electrical Signals Driven by Electromagnetic Induction

Abstract: Although adipose‐derived mesenchymal stem cells (ADMSCs) isolated from patients’ fat are considered as the most important autologous stem cells for tissue repair, significant difficulties in the neural differentiation of ADMSCs still impede stem cell therapy for neurodegenerative diseases. Herein, a wireless‐electrical stimulation method is proposed to direct the neural differentiation of ADMSCs based on the electromagnetic effect using a graphene film as a conductive scaffold. By placing a rotating magnet on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Besides, the active composite layer consists of conductive polymers [244] and additive materials such as MXene [245,246], graphene [247][248][249][250], and other low-dimensional carbon nanostructures [251][252][253]. One can investigate the potential of biodegradation in additives and dielectrics [254,255].…”
Section: Pressure Sensors For Touch Sensementioning
confidence: 99%
“…Besides, the active composite layer consists of conductive polymers [244] and additive materials such as MXene [245,246], graphene [247][248][249][250], and other low-dimensional carbon nanostructures [251][252][253]. One can investigate the potential of biodegradation in additives and dielectrics [254,255].…”
Section: Pressure Sensors For Touch Sensementioning
confidence: 99%
“…Additionally, Pampaloni et al 120 found that adding chemical agents and factors, which were generally considered as necessary conditions for the neural differentiation of specific stem cells. Guo et al 123 observed the neural differentiation of hADMSCs on graphene films under a rotating magnet, due to the conductive substrate created by graphene.…”
Section: Possible Mechanism Of the Impact Of Gfns On Stem Cell Differ...mentioning
confidence: 99%
“… 10 The application of nanotechnology and nanosystems in healthcare and biomedical devices improves the quality of this field. 11 Biofilm formation and its growth on implants cause inefficiency of their proper actions and lead to diseases that can be fatal. 12 Medical grade titanium and its alloys are used to make implants such as heart valves.…”
Section: Introductionmentioning
confidence: 99%